Smart lock / Muhammad Aizad Shuhaimi and Mohd Ridzuan Amir Fekri - Shuhaimi, Muhammad Aizad; Amir Fekri, Mohd Ridzuan (2015)
For this project, PIC microcontroller based project is designed to develop a low cost RFID lock. Before this, the RFID has been used for many purposes. One of the examples is the security door lock at the office. So the purpose for this project is to attach the RFID to the luggage which it only use combination code number before this. This is because luggage that use combination code number is easily been unlocked by people with such skill to open it. When the project is started, the RFID tag needed to be place near to RDIF reader so that the reader can read RFID tag and then send the tag ID to the PIC microcontroller. After PIC microcontroller process the data, the tag ID will display on LCD in decimal number and only particular RFID tag can pass the door lock. Therefore, Smart Lock is a technology with new improvement and innovation which will be applied in daily life application. This project could prevent people from stealing other people through pickpocket and also could make people aware of their luggage from mistakenly collected.